Pengaruh Tax Amnesty, Sanksi Perpajakan dan Kualitas Pelayanan Fiskus terhadap Kepatuhan Wajib Pajak Orang Pribadi - Shinta Devi Darmayani, A. A. Sagung; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 30 No 10 (2020)DO - 10.24843/EJA.2020.v30.i10.p01, 2020)
This study has a purpose to determine the effect of tax amnesty, tax sanctions and the quality of tax authorities on compliance of individual taxpayers that conducted at KPP North Badung. The number of sample are 100 respondents by using accidental sampling methods. Data analysis technique that used are descriptive statistical test, classic assumption test and multiple linear regression. Based on the results of testing conducted, it is known that tax amnesty, tax sanctions and the quality of tax authorities have an effect on the compliance of individual taxpayers registered in KPP North Badung. Keywords: Tax Amnesty; Tax Sanction; Service Quality; Taxpayers Compliance.